Revisión de los estudios orientados a la medición de las capacidades tecnológicas por medio de la literatura patente. Propuesta de análisis estadístico y evaluación de la calidad de una base de datos en patentes - Ayuso Sánchez, M. J.; Ayuso García, M. D. (Revista General de Información y Documentación, 2003)
The development of statistical and bibliometrics studies of patents literature were begun in Spain by various authors who will be considered later. Review has been carried out of the criteria for the creation of a database entitled Recodification. SAV for the analysis and statistical treatment of 13,913 Spanish patents deposited in the Spanish Patents and Trademarks Office.